PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN SEKTOR PERTAMBANGAN MINYAK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018) - Bambang Sugeng Dwiyanto; Sulistiono Sulistiono (STIE Pariwisata API Yogyakarta, 2021)
Stock price fluctuations are natural and almost occur in all companies in various sectors, including companies in the oil mining sector so that price changes affect the company's financial performance and stock prices which can be analyzed fundamentally using financial ratios to aspects in the financial statements. The framework of this research is to analyze the effect of financial ratios on stock prices. The population and sample used are oil mining sector companies listed on the Indonesia Stock Exchange 2014-2018. The sampling method used is purposive sampling or judgmental sampling. Sources of data used are secondary data in the form of financial statements. The tool used for data collection is through the method of observation and analysis of the company's financial statements. The results showed, based on the t test value, stock prices were positively influenced by Return on Equity (ROE), Book Value (BV) and Price to Book Value (PBV), while negatively influenced by Debt To Equity Ratio (DER) and Net Profit. Margins (NPM). Based on the F test value, stock prices are positively influenced by ROE, DER, NPM, Earnings Per Share (EPS), BV, and PBV. Based on the coefficient of determination test (R2), stock prices are strongly influenced by ROE, DER, NPM, BV, and PBV by 91.5% and influenced by other variables by 8.5%.